Entrepreneurial rise in the Middle East and North Africa : the influence of quadruple helix on technological innovation - Sindakis, Stavros; Aggarwal, Sakshi (Advanced strategies in entrepreneurship, education and ecology., 2022)
Entrepreneurship is an essential driver for economic growth and innovation. With the Middle East and North Africa (MENA) economies implementing reforms to improve employment, growth, diversification, governance structures, private sector development, the ecosystem encouraging MENA's digital entrepreneurship potential has been falling into place to unlock all its entrepreneurship potential. Entrepreneurial Rise in the Middle East and North Africa shares contributions from researchers and practitioners in a wide variety of fields related to the relationships and inter-dependencies between innovation, political regimes, and economic and social development throughout the MENA region. Chapters explore innovations across these varied sectors, emphasising on the discovery of emerging patterns and catalysts to these innovations and their impact on future research, practice, and policy. The Quadruple Helix model describes this new economic environment with examples throughout the MENA region on how government, universities, companies, civil society/community support innovation. Examining these unique start-up scenes, Entrepreneurial Rise in the Middle East and North Africa: The Influence of Quadruple Helix on Technological Innovation will be beneficial for upcoming students, entrepreneurs, and researchers interested in the concepts of the Quadruple Helix model of innovation, tech start-ups, and entrepreneurship rise in the Middle East and North Africa.